1989
DOI: 10.3109/00016488909107396
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Investigations in Hypothyroidism

Abstract: Twenty patients with thyroprivic hypothyroidism with a mean age of 34.8 years (range: 15-50 years) were investigated. Peripheral/central functions of the auditory system were assessed in the hypothyroid state and they were re-evaluated in the euthyroid state after treatment with levothyroxine. The mean observation period for re-evaluation was 3.7 months (range 3-7 months). Sixteen patients with hypothyroidism (80%) demonstrated hearing loss when compared with randomly selected age- and sex-matched normal subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
3
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 13 publications
11
41
3
7
Order By: Relevance
“…A maioria dos trabalhos realizados em adultos com hipotireoidismo clínico submetidos a ABR resultaram em evidências de aumento de LA V e da LIP I-V. [19][20][21]23 Alguns também encontraram alargamento da LIP I-III. 19,20 Outros autores ainda acharam prolongamento da LIP III-V. 23 Aqui, vale a pena ressaltar que todos os pesquisadores acima mencionados enfocaram o hipotireoidismo clínico, enquanto que nós nos reportamos à forma subclínica da doença.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A maioria dos trabalhos realizados em adultos com hipotireoidismo clínico submetidos a ABR resultaram em evidências de aumento de LA V e da LIP I-V. [19][20][21]23 Alguns também encontraram alargamento da LIP I-III. 19,20 Outros autores ainda acharam prolongamento da LIP III-V. 23 Aqui, vale a pena ressaltar que todos os pesquisadores acima mencionados enfocaram o hipotireoidismo clínico, enquanto que nós nos reportamos à forma subclínica da doença.…”
Section: Discussionunclassified
“…19,20 Outros autores ainda acharam prolongamento da LIP III-V. 23 Aqui, vale a pena ressaltar que todos os pesquisadores acima mencionados enfocaram o hipotireoidismo clínico, enquanto que nós nos reportamos à forma subclínica da doença. Ou seja, nossos resultados apontam para o fato de mesmo quando a insuficiência tireóidea ainda não atingiu seus estágios mais desenvolvidos, já poderá ocorrer distúrbio de condutibilidade nervosa auditiva central, caracterizado por atraso na propagação do estímulo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In addition to thyroid dysfunction, HT can cause various otological symptoms. Although these abnormalities can occur as a direct consequence of hypothyroidism [1], it has been suggested that the circulating antithyroid autoantibodies can lead to T-cell mediated vestibulocochlear dysfunction. A review of the literature shows various case studies documenting the association of these two autoimmune entities [1215] which demonstrate the existence of a clear relationship between thyroid autoimmunity and the inner ear damage, regardless of thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Hashimoto’s thyroiditis (HT) are at higher risk of developing audiological abnormalities as compared to the healthy individuals [1]. This auditory dysfunction can be multifactorial as indicated by case studies done on HT.…”
Section: Introductionmentioning
confidence: 99%